(untitled) (International Journal of Engineering and Computer Science, 2014)
The concept of data hiding mainly focuses on embedding messages within the other. Many transformations have been made in Least Significant Bit (LSB), but it is a traditional approach. Challenges still remain in storing or embedding text data in images without image distortion. The proposed technique provides a solution for data embedding along with the image security by encrypting the image with the key generated by block permutation. The process of encrypting the given image with the key makes the image to be secure in transmission. In this paper, a novel scheme for separable reversible data hiding in encrypted image is proposed, which consists of image encryption, data embedding and data-extraction / image-recovery phases. The input image is obtained from the user and it is converted to gray scale. A key is generated to perform image encryption. Image encryption involves a sequence of steps viz. key permutation, pixels shuffle, block shuffle, height and width shuffle. The final image obtained is used for data hiding. The text to be hidden is encrypted and the position to hide the data is chosen based on the main key. When the receiver has both of the keys, the hidden data and the original image can be obtained.